Habitat Protection Approaches Facilitate Conservation of Overlooked Fungal Diversity – A Case Study From the Norwegian Coastal Heathland System - Blaalid, Rakel; Davey, Marie L. (Frontiers in Fungal Biology, 2022)
European coastal heathlands are distinct ecosystems shaped by land use tradition and they have experienced an 80% area reduction from their historical maximum. These mosaics of mires and wind exposed patches have ericaceous shrub dominated vegetation, and soils within coastal heathlands are characterized by low pH and high levels of recalcitrant debris. Using a culture-based approach with molecular identification of isolates, we characterized root-associated fungal communities of six ericaceous species in eight heathland localities along Norway’s western coast. Site-level alpha diversity ranged from 21-38 OTUs, while the total estimated gamma diversity for culturable heathland root fungi was 190-231 OTUs. Most species recovered are previously reported at low abundance in Norway, suggesting the biodiversity in this community is underreported, rather than novel for science. The fungi recovered were primarily Ascomycota, specifically endophytic Phialocephala, and Pezicula, and no host specificity was observed in the communities. The fungal communities exhibited high turnover and low nestedness, both between ericaceous hosts and across heathland sites. We observed no spatial patterns in fungal betadiversity, and this heterogeneity may be a product of the unique historic land use practices at each locality creating a distinct mycofloral “fingerprint”. Robust diversity estimates will be key for managing fungal biodiversity in coastal heathlands. Our results indicate that sampling schemes that maximize the number of host plants sampled per site, rather than the number of cultures per plant yield improved alpha diversity estimates. Similarly, gamma diversity estimates are improved by maximizing the total number of localities sampled, rather than increasing the number of plants sampled per locality. We argue that while the current protected status of coastal heathland habitats and restoration efforts have knock-on effects for the conservation of fungal biodiversity, fungi have a vital functional role in the ecosystem and holistic conservation plans that consider fungal biodiversity would be beneficial.